LC-MS/MS methods for the quantification of sulfasalazine and sulfapyridine in various matrices: application to a pharmacokinetic study - Louw, Vanessa (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc) -- Stellenbosch University, 2022.